Designing Quizizz as Media to Assess the Mastery of Simple Past Tense - Billy Hermanto; Sudarsono Sudarsono; Yanti Sri Rezeki (FKIP - Universitas Tanjungpura, 2023)
This research study aimed to design Quizizz as media to assess the mastery of simple past tense to year-8 students of SMP Kristen Immanuel 1 Pontianak. The form of this research study was development research. The research used the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model. However, due to the COVID-19 pandemic, the researcher did three phases in this study: Analyze, Design, and Develop (ADD). In the analysis phase, the researcher interviewed the English teacher to find out the actual conditions of the students, the teacher, and the school. In the designing phase, the researcher observed the textbook and the curriculum applied in the school to design a significant product of Quizizz. During the development phase, the researcher used the Quizizz platform to develop the learning media for the students by combining multimedia such as images, GIFs, videos, and sounds. Then, the designed product was completed after having two internal evaluations to ensure that the product was usable and fulfilled all the assessment criteria. In conclusion, the Quizizz multimedia assessment assesses the mastery of simple past tense for year-8 students of SMP Immanuel 1 Pontianak.